Determinants of infectious disease in children: Epidemiological Phenomena - Yarmaliza Yarmaliza; Teungku Nih Farisni; Fitriani Fitriani; Zakiyuddin Zakiyuddin (ITKES Wiyata Husada Samarinda, 2020)
Diarrhea is a disease with changes in the shape and concentration of feces, which softens until melted, and increases the frequency of bowel movements more than normal (3 times or more a day). Data from Tanoh Manyang Village in 2014 showed the proportion of diar-rhea in infants was 12% of 144 children, in 2015 26% of 156 children, in 2016 as many as 40% of 343 children. The purpose of this study was to determine the effect of maternal culture on the incidence of infectious diseases (diarrhea) in infants. The population in this study 138, with sampling using total sampilng. This type of analytic survey research with cross sectional approach, data analysis using univariate, bivariate, and multivariate. Chi-square test results showed that mothers 'knowledge and attitudes as well as clean and healthy life behaviors of mothers affected the incidence of diarrhea in infants (p <0.05), while the results of multivariate logistic regression tests showed that mothers' clean and healthy life behavior had a stronger influence on incidence of diarrhea in toddlers with Exp (B) value of 38, 201. Conclusions from the results of multivariate regression tests the mother's clean and healthy behavior has a strong influence on the incidence of diarrhea in infants. It is suggested that related agencies can increase health promotion in the form of counseling to the community so as to increase knowledge of clean and healthy living behavior in preventing infectious diseases, especially the incidence of diarrhea in infants.